The Analysis of Healthy Lifestyle Mechanisms in Overcoming Stress on Public Accountant Firm Auditors - Prasetyo, Rezky Eko; Hoesada, Jan (International Journal Labs, 2023)
The problem of stress often occurs in auditors who work in Public Accountant Firms, especially during a peak season. Several previous studies showed that role stress hurts job outcomes. To overcome this, this research tries to provide a solution and test whether a healthy lifestyle mechanism (healthy lifestyle, vitality, and psychological well-being) can minimize the negative impact of role stress (role ambiguity, role conflict, role overload, and job burnout) to job outcome (job satisfaction, performance, turnover intentions, and organizational commitment). The results of this study indicate that a healthy lifestyle mechanism can minimize the negative impact of role stressors on job satisfaction and organizational commitment. However, this study has not been able to prove that a healthy lifestyle mechanism can reduce the auditor's desire to shift work and improve auditor performance. This study also shows the results that job satisfaction can reduce the auditor's turnover intention and organizational commitment is not a factor that can reduce that intention.